Association between serum 25-hydroxyvitamin D concentrations and hypertension among adults in North Sudan: a community-based cross-sectional study - Ahmed A. Hassan; Omer Abdelbagi; Osman E. Osman; Ishag Adam (BMC Cardiovascular Disorders, 2023)
Abstract Background Globally, hypertension represents a major public health problem. The association between 25-hydroxyvitamin D (25[OH]D) levels and hypertension remains unclear. The current study aimed to investigate the association between serum 25(OH)D levels and hypertension among adults in Sudan. Methods A community-based cross-sectional study was conducted among adults in North Sudan. Sociodemographic and clinical data were collected using a questionnaire and face-to-face interviews. Serum 25(OH)D was measured using an enzyme-linked immunosorbent assay. Multivariate logistic regression and multiple linear regression analyses were performed. Results Of the total of 391 participants, 202 (51.7%) were females. The median (interquartile range [IQR]) of participants’ ages was 45(32–55) years. Of the total, 219(56.0%) had hypertension. The median (IQR) of serum25(OH)D was 13.3(9.9–19.7) ng/mL, and 295 (75.4%) participants had vitamin D deficiency (< 20 ng/mL). In multivariable logistic regression, the adjusted odds ratio (AOR) for age = 1.05, 95% confidence interval (CI)1.03‒1.061, the AOR for being female = 2.02, 95% CI, 1.12‒3.66, and body mass index was AOR = 1.09, 95% CI, 1.05‒1.14, all of which were significantly associated with hypertension. However, serum 25(OH)D levels were not associated with hypertension (AOR = 1.01, 95% CI 0.99‒1.05, P = 0.317). In multiple linear regression, while systolic blood pressure was negatively associated with 25(OH)D (coefficient = − 0.28, P = 0.017), there was no significant association between serum 25(OH)D level and diastolic blood pressure (coefficient = − 0.10, P = 0.272) or mean blood pressure (coefficient =–0.03, P = 0.686). Conclusion The current study revealed a negative association between vitamin D and systolic blood pressure. The mechanism of such an association needs further study.